Public perception and behavior toward butterfly diversity and benefits in Bandung, West Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Fitriani N, Supangkat B, Hermawan W, Iskandar J, Abas MA. 2025. Public perception and behavior toward butterfly diversity and benefits in Bandung, West Java, Indonesia. Biodiversitas 26: 5089-5108. Butterflies, with their ecological, cultural, and economic benefits, yet public understanding of their roles in Indonesia remains limited. This study assessed community Knowledge, Attitudes, and Behaviors (KAB) toward butterflies in Bandung, West Java, Indonesia. A mixed-method approach was applied through structured and semi-structured interviews with 100 respondents, complemented by butterfly diversity surveys across 31 urban-to-rural transects. The quantitative data were analyzed using Spearman’s rho and Chi-square tests (N: 100, p
Keywords: Bandung, biodiversity, butterflies, folk taxonomy